Comprehensive analysis of fly ash induced changes in physiological/growth parameters, DNA damage and oxidative stress over the life cycle of Brassica juncea and Brassica alba. (November 2017) - Jana, Aditi; Ghosh, Manosij; De, Arpita; Sinha, Sonali; Jothiramajayam, Manivannan; Mukherjee, Anita
Abstract: Fly ash (FA) being a heterogeneous mixture of heavy metal affects plant system in various ways. Previous studies have shown bioaccumulation of toxic metals in the plants and disturbance in cellular activities. Here, we have studied the impacts of FA treatment through the life cycle of economically important, annual crop plant mustard ( Brassica juncea and Brassica alba ). Result revealed that FA did not alter germination rate and photosynthetic pigment levels. Tolerance index of B. juncea was higher compared to B. alba . Seed setting was significantly affected by FA in B. alba. Significant increase in DNA damage was observed in both B. alba and B. juncea . Proline accumulation was significantly higher in B. alba . In B. juncea catalase activity and reduced glutathione content declined in initial days which were restored at the end of experimental period. Significant decrease in non-enzymatic antioxidants was noted in B. alba . Higher accumulation of Pb and As was noted in shoot of B. juncea and in B. alba Cu, Pb, Cr and As accumulated in shoots. As observed from these results, both plants could translocate certain toxic heavy metals from roots to the shoot which affected the physiological and biochemical balance and induced genotoxic response. Graphical abstract: Highlights: Fly ash (FA) was phytotoxic and affected the seed production in B. alba . The oxidative imbalance resulted in significant DNA damage. Brassica juncea was a potent phytostabilizer. Brassica alba can perform as phytoextractor of heavy metals. Translocation of toxic heavy metals take place from roots to shoots.